Synthesis of Nonnatural Amino Acid Derivatives with Ni Complexes and Investigation of the Antifungal Activity of Their Dipeptide Derivatives - Hakobyan, Hegine I.; Khachaturyan, Nune; Gevoryan, Sona; Sargsyan, Tatevik H.; Danghyan, Yuri M.; Saghyan, Ashot S.; Zakarian, Armen; Mardiyan, Zorayr Z. (Synlett, 2025)
A convenient synthesis of optically pure (S)-2-amino-3-(1-benzyl-1H-1,2,3-triazol-5-yl)-2-methylpropanoic acids via propargylated amino acids is reported. An (S)-2-amino-2-methylpent-4-ynoic acid–Ni–N-(2-benzoylphenyl)-1-benzyl-l-prolinamide complex was prepared and then functionalized by click-coupling reactions to give the corresponding (S)-2-amino-3-(1-benzyl-1H-1,2,3-triazol-5-yl)-2-methylpropanoic acid Ni complexes. Subsequently, these Ni complexes were cleaved to obtain the free (S)-2-amino-3-(1-benzyl-1H-1,2,3-triazol-5-yl)-2-methylpropanoic acids with excellent optical purities. Next, by using the activated ester method for peptide synthesis, N-Fmoc-(S)-(2-amino-3-(1-benzyl-1H-1,2,3-triazol-4-yl)-2-methylpropanoyl)glycine dipeptide was prepared. The nonnatural amino acids and dipeptides were tested for their biological activity and showed a selective high inhibitory activity against fungi.
Keywords: nickel complexes; asymmetric alkylation; amino acids; antifungal agents